Konsep Penterjemahan Sifat Salbiyyah dan Ma`ani Menurut Wan Ismail al-Fatani (Pak Da Ail) dalam Matan Bakurah al-Amani: Translation Concept of Salbiyyah and Ma`ani according to Sheikh Wan Ismail al-Fatani (Pak Da Ail) in His Work Bakurah al-Amani - Dahlan, Mansor; Abd Latif, Faizuri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Malay scholars are among those who strive to spread the truth of faith to their society. Their contributions are not only focused on learning institutions, even they are also active in producing works in various Islamic disciplines such as of `Aqidah, Jurisprudence, Sufism and others. Considering the question of faith is the most important and major issues in Islam, it has attracted Malay scholars’ attentions in underlining its discussion in their works. The most related issues discussed are the 20 attributes of God (Sifat 20). In enhancing the understanding of those attributes, there are some Malay scholars who lay emphasis on the aspects of linguistic that become the core feature in understanding the true meaning of the Arabic terms. Sheikh Wan Ismail al-Fatani (Pak Da Ail) was among those who applied a systematically approach of translation in elucidating the attributes concerning Salbiyyah and Ma`ani. The approach indeed can be implemented with in-depth knowledge in Arabic. His expertise in the syntax allowed him to carry out the translation works in accordance with the grammar structure aimed to presenting the exact and true meaning of the words and phrases, although it looks awkward because it does not conform to conventional methods used by scholars in Malay Archipelago.